Analysis of HPV vaccine coverage in university students of Cascavel (Paraná) (Research, Society and Development, 2023)
Objective: This study aimed to verify the students' support the HPV vaccination campaign, their previous knowledge about the virus, related diseases and vaccination itself.  Methods: We interviewed 115 students from a public and a private institution from several courses. The interviews took place through Google Forms, which contained 15 objective questions related to the HPV vaccination campaign, knowledge about the topic and the reasons for the campaign's adhering or not.  Results: Among the results, it was found that 52.07% of the participants had complete HPV vaccination, 57.85% of which came from public health. Among the main reasons for the support was the search for protection against diseases, the choice to vaccinate and the encouragement of schools. Conclusion: It was concluded that there is significant vaccination coverage among the candidates, having the school an extremely important role in awareness and guidance related to the virus, related diseases and the importance of vaccination.